(untitled) (Journal of Economic Research & Business Administration, 2015)
Questions of application of projects management methodology in educational activity of higher school are considered in the article. In this regard, there was a carrying out questioning of the teaching staff, educational support personnel and chairs/divisions direction of higher education institution. Actual problems of educational activity management are revealed,which, in particular, are connected with difficulties of the organization of communications between the management of chair and its employees, and also with problems of the organization of performance of qualification student’s works in due time. Project management is relative new methodology in conditions of Kazakhstan which got recently great value for management of projects in the most various spheres of activity. That fact is remarkable that the majority of respondents supported need of introduction of tools and methods of project management in education.